Hydroxylation Reaction on Bio-lubricant Characteristics : A Case Study on Palm Kernel Oil - Fatmayati Fatmayati; Razita Hariani; Nur Asma Deli (Universitas Islam Raden Rahmat, Malang, 2025)
Historically, lubricants have relied on petroleum derivatives, but depleting resources necessitate alternatives. Vegetable oils are unstable for use due to oxidation but can be improved via chemical modification. This study examines bio-lubricant production from palm kernel oil, focusing on hydroxylation reaction time and compliance with SNI 06.7069:2012 standards. The production of bio lubricants in this study comprised three distinct stages: hydrolysis, epoxidation, and hydroxylation. Hydrolysis involves the processing of palm kernel oil to yield fatty acids and glycerol. Subsequently, the fatty acids produced during the hydrolysis reaction were epoxidized to yield the epoxy compounds. Subsequently, the epoxy compound is subjected to hydroxylation, resulting in the formation of a polyol compound that serves as the fundamental building block for the bio lubricants. Optimal bio lubricants outcomes were achieved with a hydroxylation reaction time of 240 min, resulting in a bio lubricants yield of 92.67, a kinematic viscosity value of 48.54 Cst at 313.15°K/40°C, a kinematic viscosity value of 10.89 Cst at 373.15°K/100°C, a viscosity index of 224, and a corrosion rate of 0.1496 mpy. The quality of the bio lubricants produced in this study was in accordance with the SNI 06.7069:2012 standard.